Histomorphological Features of Colon of Guinea Pig in Postnatal Age Groups - K. Raja; S.Rajathi; S.Ushakumary; Geetha Ramesh; Ramesh S.; K. Kumar; N. Hemavathi (Indian Journal of Veterinary Anatomy, 2024)
The present histological study on colon was conducted on different postnatal age groups of guinea pig. The wall of the colon (proximal and distal colon) histologically composed of the four layers namely viz., tunica mucosa, sub mucosa, muscularis and serosa. Tunica mucosa was thrown into mucosal folds. Mean height of the columnar cells in surface epithelium of small and large intestine was found to increase as the age advanced. Similarly, the mean thickness of tunica muscularis of colon was found to be increased as the age advanced. Tunica mucosa was thrown into mucosal folds. Lamina propria was composed of the loose connective tissue with crypts of the Lieberkuhn. Tunica submucosa was made up of more number of collagen and reticular fibres and few elastic fibres in the wall of the blood vessels. Tunica muscularis was lined by the inner circular and outer longitudinal muscular layer. The mean height and width of the mucosal folds and height of the columnar cells, the mean thickness of the tunica submucosa and thickness of the tunica muscularis was increased as the age advanced in all the age groups studied.